Systematic Review: Faktor-Faktor yang Mempengaruhi Kesehatan Mental Remaja di Indonesia - Amanda Dea Qur’annisya; Siti Halimatul Munawarah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Due to the growing prevalence of psychiatric conditions over the past few years, the mental well-being of adolescents has emerged as a significant public health challenge. Findings from the I-NAMHS 2023 reveal that over 33% of the adolescent population encountered mental health difficulties during the past 12 months. This condition is influenced by various interrelated determinants, both at the individual and environmental levels. The objective of this research was to examine the various factors influencing adolescent mental well-being in Indonesia through a systematic literature review. A comprehensive search was carried out across Google Scholar, ScienceDirect, and PubMed to identify academic papers written between 2020 and 2025, focusing on quantitative cross-sectional studies involving adolescents aged 10–19 years. Guided by PRISMA protocols, the methodological rigor of the selected literature was assessed via the JBI Critical Appraisal Checklist. Ultimately, from a pool of 1,825 retrieved articles, 21 met the inclusion standards and were subsequently analyzed. The findings indicate that adolescent mental health is influenced by internal factors such as sex, history of chronic illness, genetic predisposition, personality type, and lifestyle, as well as external factors including parenting style, social support, academic stress, experiences of bullying, socioeconomic status, digital media use, and educational environment. This study underscores that teenager mental well-being is determined by multi-level interactions, necessitating multifaceted interventions at personal, family, and community levels.